1974
DOI: 10.1161/01.cir.49.2.326
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Subendocardial Ischemia in Severe Valvar and Supravalvar Aortic Stenosis

Abstract: Severe valvar aortic stenosis (VAS) and supravalvar aortic stenosis (SVAS) each may cause left ventricular (LV) subendocardial ischemia and infarction, even with patent coronary arteries. LV ischemia in VAS has been related to reduced coronary perfusion relative to raised metabolic requirements, whereas this mechanism of ischemia has not been widely accepted in SVAS because coronary perfusion pressure is higher than normal.LV subendocardial coronary blood flow (CBF) occurs predominantly in diastole and a diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…34,35 Huysman et al reported that the volume fraction of nonmyocyte tissue in the subendocardial myocardium increased as heart weight increased, independent of the type of pressure overload. 36 Therefore, in patients with POH, increased subendocardial connective tissue may result in lower CVIB values in endocardial ROIs.…”
Section: Cvib In the Hypertrophied Myocardiummentioning
confidence: 99%
“…34,35 Huysman et al reported that the volume fraction of nonmyocyte tissue in the subendocardial myocardium increased as heart weight increased, independent of the type of pressure overload. 36 Therefore, in patients with POH, increased subendocardial connective tissue may result in lower CVIB values in endocardial ROIs.…”
Section: Cvib In the Hypertrophied Myocardiummentioning
confidence: 99%
“…In patients with left ventricular hypertrophy (LVH), it has been reported that myocardial ischemia may occur in the absence of epicardial coronary artery disease (1)(2)(3)(4)(5). It has been suggested that an imbalance between oxygen supply and demand due to the greatly increased myocardial mass might be a mechanism for myocardial ischemia (6).…”
Section: Introductionmentioning
confidence: 99%
“…7,9,17 Patients with Williams syndrome have increased mortality associated with cardiac catheterization caused by coronary artery stenosis 2,3 or subendocardial ischemia arising from hemodynamic perturbations in the setting of ventricular hypertrophy. 28 Both of these factors accounted for the 3 deaths in our series. There were no deaths after 1993 in the final 14 patients.…”
Section: Complicationsmentioning
confidence: 71%